Non-mechanical optical beam-steering of a liquid crystal laser. (January 2023) - Zhang, Guanxiong; Elston, Steve J.; Schreier, Andy; Faulkner, Grahame; Surampudi, Atchutananda; O'Brien, Dominic; Morris, Stephen M.
Highlights: Two-dimensional optical beam-steering of a band-edge liquid crystal laser. No variation in wavelength; minimal impact on the intensity. Liquid-crystal-polymer-based configuration and dynamic electrical control. Demonstration of simulating imperfections in the polarisation grating structure. Abstract: In this paper, we demonstrate dynamic optical beam-steering of a band-edge chiral nematic liquid crystal (LC) laser that does not involve any change in the configuration of the helical structure. This beam-steering is achieved by exploiting the circular polarisation of the LC laser in combination with tuneable nematic LC phase shifters and fixed polarisation gratings. Experimental results are presented, showing the optical steering of the LC laser emission to four separate discrete spatial positions and, using simulations based on Jones calculus, we explain the appearance and relative intensities of other minor spots that appear around the primary beam. Compared with other approaches of beam-steering an LC laser, this method does not result in an alteration of the laser wavelength, does not change the internal cavity structure of the laser, and has a minimal impact on the intensity of the laser emission. In addition, the whole system (except for the solid-state pump source) is comprised of thin films that are either liquid crystalline or polymers, which provides a tangible route towards a more compact and integrated optically steerable LC laser.